The Cambridge edition of the correspondence of Daniel Defoe - Defoe, Daniel 1660-1731 (Cambridge University Press, 2022)
This comprehensive and authoritative edition of the correspondence of Daniel Defoe situates each letter in its biographical, literary, and historical contexts. A unique source for a turbulent period of British history, Defoe's correspondence spans topics including the first age of party marked by Tory and Whig rivalry, religious tensions between the Church and Dissenters, the uncertainty of the monarchical succession, the birth of Great Britain and its establishment as a global empire, and the use of the press to mould public opinion. As well as an introduction discussing Defoe's epistolary habits and the distinctive features of his letters, headnotes and annotations explain each document's occasion, beginning in 1703 with Defoe hunted by the government for sedition, and ending in 1730 with him again in hiding, fleeing creditors months before his death. The volume is illustrated with examples of Defoe's letters, offering a fresh window onto Defoe's manuscript habits
Title from publisher's bibliographic system (viewed on 09 Sep 2022)
Keywords: Defoe, Daniel / 1661?-1731 / Correspondence; Authors, English / 17th century / Correspondence; Authors, English / 18th century / Correspondence; Briefsammlung